Effect of Chickpea Straw Silage Processing with Urea, Molasses and Cellulase Enzyme on Chemical Composition, Gas Production, Ruminal and intestinal Digestibility - Zahra Abbasinavand; Jamal Seifdavati; Mojtaba Alipour einaldin; hossein abdibenemar; Farzad Mirzaei Aghjehgheshlagh; reza seyedsharifi (پژوهشهای علوم دامی ایران)
Introduction: The limitation of animal feed resources has increased the tendency to use agricultural residues such as straws in feeding ruminants. It has been reported that livestock production decreases when using low-quality crop residues due to the low palatability, energy level and protein of these feed materials. In other hand, high consumption of straws decreases ruminant's performance because of feed intake restriction, low digestibility and the presence of anti-nutritional factors such as silica, tannin and lignin in straws. The use of fibrolytic enzymes of foreign origin increases the usability of forage, which results in increased production. One of the most important methods of processing wooden materials is the use of chemicals, especially alkaline materials, especially urea. Adding molasses as an energy-generating part and urea as a non-protein nitrogen source simultaneously provides the rumen microorganisms with a source of energy and protein. In general, the addition of enzymes to the diet is used for the purpose of supplementing and compensating the defects of the enzyme system of the ruminant’s digestive system, removing anti-nutritional substances and increasing the availability of nutrients in the animal body. The purpose of this research was to investigate the effect of processing chickpea straw with urea, molasses and enzymes on chemical composition, ruminal and intestinal digestibility, gas production and disappearance under laboratory conditions. So that the results of this research can be optimally used in animal nutrition.Materials and Methods: This research was conducted on processed chickpea straw with urea, molasses and, enzyme source of fungal cellulase and rumen liquid. The tested feed material was chickpea straw, which was processed with urea, molasses and enzymes. Enzymes included fungal cellulase and rumen liquid. The tested feed ingredients were ground using a special mill with a sieve with 2 ml pores and then sieved using a 50 micrometer sieve to remove particles smaller than 50 micrometers.To perform the gas test, first, the sample of the tested feed (chickpea straw enriched with urea, molasses and enzyme) was ground with a 1 mm grid. Measurements of chemical composition and gas production were carried out by standard methods and the determination of the digestibility of samples was done with Daisy ǁ device and Gargalo's three-step method. After performing the initial calculations and collecting all the data, statistical analysis of the data was done using the SAS statistical software in the form of a completely random design and a 4x4 factorial experiment with the GLM procedure.Results and Discussion: According to the results, processing chickpea straw with urea, molasses, and enzymes increased the percentage of dry matter and the amount of crude protein in the treatments. However, it decreased the percentage of cell wall and cell wall without hemicellulose. The processing of chickpea straw with urea, rumen liquid and a mixture of two enzymes and the combination of all three enzymes with a level of 4% molasses increases the digestibility of dry matter in the total digestive system, and the addition of molasses and the combination of rumen liquid and a mixture of two enzymes with different levels of molasses were increased the digestibility of crude protein in the rumen (P<0.05). Adding all three enzymes to chickpea straw at 2, 4, 6, and 8 hours, but with rumen juice from 12 to 96 hours, has led to an increase in gas production. The combination of molasses levels of 2 and 4% with a mixture of two enzymes increased gas production in all hours of incubation (P<0.05). The average constant rate of disappearance and gas production potential of chickpea straw was significantly different among all treatments (P < 0.05). The results showed that molasses and enzyme increased the constant rate of disappearance and 4% molasses and enzyme increased the gas production potential. The combination of molasses with fungal cellulase and the mixture of two enzymes decreased the constant rate of disappearance and gas production potential. The average laboratory digestibility of organic matter, metabolizable energy, lactation energy and short chain fatty acids were significant in all chickpea straw treatments (P < 0.05).Conclusion: In general, based on the obtained results, the use of urea, molasses, and enzyme sources including fungal cellulase and rumen liquid has successfully increased the nutritional value, gas production parameters, and digestibility of chickpea straw. Among the experimental treatments, processing chickpea straw with 3.5% urea, 4% molasses, and fungal cellulase enzyme improved the nutritional value the most. Further animal experiments are needed to confirm these results. More research is required in the field of using agricultural waste in animal nutrition.